THE USE OF KWL (KNOW-WANT-LEARN) TECHNIQUE TO INCREASE THE ABILITY OF THE SECOND GRADE STUDENTS OF SMA N 5 PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Novia Tri Febriani Tri Febriani; Syofia Delfi Delfi; Desri Maria Sumbayak Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Teachers tend to increase the students’ ability by appliying techniques in teaching and learning process. One of them is as the topic of this article. This article is based on a research report about using KWL technique to increase the students’ ability in comprehending narrative texts. The purpose of this research is to find out whether or not using KWL technique could increase students’ ability in comprehending narrative texts and factors that could increase the ability. Classroom action research was designed in two cycles at XI IPS 2 of SMA N 5 Pekanbaru as the participant of this study. The data were collected through tests and observation sheets. This research found that KWL technique could increase the students’ ability in comprehending narrative texts. The average score of the data increased from 62,3 in pre-test, 72,3 in post-test I, and 80,3 in post-test II. It is in line with the students’ observation sheets in which there were also improvements in the students’ activeness during the teaching and learning process. The data showed that the average score of students’ activeness in cycle I was 58,5% and increased in cycle 2 to 87,5%. Based on the writer’s observation, the improvement of the students were due to some factors dealing with the KWL technique. They were using chart, leading the students to think independently, and making the students became more active. This study suggests that the students can apply this tekhnique continuously in learning reading subject. Moreover, the teacher should be able to manage the time, so the teaching and learning process will be going effectively. In addition, it is expected that other researcher will conduct this technique in other genre of the texts.Key words: KWL technique, reading ability, narrative texts